Preliminary study on Gongronema latifolium stems fibers as a renewable engineering material for reinforcing polymer composites - Okafor, Christian Emeka; Ugwu, Peter Chukwuemeka; Ekwueme, Godspower Onyekachukwu; Akçakale, Nürettin; Ifedigbo, Emmanuel Ekene; Madumere, Augustine Uzodinma (Budapest International Research and Critics University, 2025)
The ultimate analysis of Gongronema latifolium plant stem fibers was conducted to evaluate their potential as a renewable engineering material. The study utilized Gongronema latifolium plant fibers sourced from a local farm in Anambra State. Lignin determination was done by using 0.3 g samples prepared alongside 0.3 g for cellulose and crude fiber analyses. Key chemicals used included 72% sulfuric acid for lignin extraction and petroleum ether for defatting. Standard laboratory glassware and equipment, including a muffle furnace for ash content determination and an electric oven for drying, were employed. Ash content was determined from the incineration of 2 g of fibers at 800 °C and the bulk density was determined using a pycnometer. Moisture content was determined through oven drying while crude fibre was carried out using Association of Official Analytical Chemists (AOAC) procedure where sample was treated with refluxing acid and alkali solutions of sulfuric acid and sodium hydroxide respectively. Cellulose content was determined via the Crampton and Mayrand method, involving centrifugation and acid digestion. Samples for lignin content determination were subjected to 72% sulfuric acid hydrolysis and weights obtained were used for calculation of lignin. The percentages of cellulose content were 12.862%, lignin 10.301%, and hemicellulose 6.005%. The moisture content of stem fibers was determined to be 1.711% from a sample weight of 1.344 g. The ash content was calculated at 10.095% from a sample of 1.466 g. Additionally, the fiber content was found to be 4.249% from a sample weight of 1.624 g, while the bulk density was measured at 0.417 g/ml. These findings indicate a favorable composition for reinforcing materials in composites and other engineering applications. As the findings have revealed, fibers obtained from Gongronema latifolium have notable potential in being used as the substitutes to the conventional engineering materials that would pave way for the creation of environmentally friendly products in the field of material engineering. Further studies are recommended to explore the processing techniques and performance characteristics of these fibers in reinforced composite applications.